The Implied Meaning of Bruno Mars’ Album 24k Magic - Andy Amirudin; Revisi Lugu (Jurnal Ilmiah Langue and Parole, 2025)
This research investigates the implicit meanings found in the lyrics of Bruno Mars’ 24K Magic album. It examines the artist’s use of figurative language and cultural references to deliver underlying themes associated with lifestyle, self-confidence, affection, and identity. The objectives of this research are to identify the implied meanings in the song lyrics, to analyze how themes such as lifestyle, affection, and cultural identity are implicitly represented, and to examine the elements that contribute to the construction of these meanings within the lyrics. This research focuses on how the artist uses figurative language and cultural references to convey hidden themes related to lifestyle, self confidence, affection, and identity. The research adopts a qualitative descriptive approach, utilizing semantic analysis and contextual interpretation to examine the lyrical content of each track. Data were obtained through a documentation method, drawing from credible and official lyric sources. The results indicate that symbols of wealth such as gold, luxury clothing, and festive imagery function not just as material representations but as metaphors for personal empowerment and self representation. Moreover, expressions of love and admiration are conveyed through poetic devices, adding depth to the album's artistic expression.This research offers insight into the intersection of music, literature, and culture, demonstrating how popular music especially in the R&B and funk genres can reflect complex personal and social themes. The research uncovering the hidden messages within the album’s lyrics, the research promotes a richer understanding of how mainstream artists like Bruno Mars embed layered meanings in their musical works